Pengaruh Keikutsertaan Mahasiswa pada Organisasi Mahasiswa Terhadap Indeks Prestasi - Rahman, Nurir; Abdullah, A. Fatikhul Amin (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to determine the level of participation of the 2021 cohort in the HMPS TIPS organization and to assess the cumulative grade point average (GPA) of the 2021 cohort, as well as to identify the influence of student participation in student organizations on academic performance. The research method used in this study is quantitative research with an ex post facto approach. The data collection technique in this study involved questionnaires distributed to respondents representing a specific population.The results of the study are as follows: 1)The participation level of the 2021 cohort in the HMPS TIPS organization is 0.62, which falls into the high category. Among the participants, 17 students are categorized as high, 6 students as low, and 3 students as very high. 2)The cumulative GPA of the 2021 cohort shows that the majority of students experienced an increase in GPA after participating in the organization, with 12 students showing an increase, while 10 students experienced a decrease, and 4 students maintained their GPA. Based on the cumulative GPA for semester 7, the 2021 cohort experienced a decline from their GPA in semester 5, with 24 students analyzed. However, when categorized by GPA, 21 students fall into the satisfactory category (80%), while the remaining 5 students are in the very satisfactory category (20%). 3)The hypothesis test results indicate that there is no significant influence of organizational participation on academic performance. The calculated t-value is 0.113, which is smaller than the t-table value of 2.064. This is further supported by the significance level of 0.911, which is greater than 0.05. Therefore, this means that the null hypothesis (H0) is accepted and the alternative hypothesis (H1) is rejected